Digitalizing MSME Financial Management through Financial Applications in the Pondok Indah Housing Area, RW 09, Kutabumi Village, Tangerang Regency - Anggi Amalia Putri; Bace Arliati Tunliu; Fanji Muchlisina; Risah Hartanti; Holiawati Holiawati; Endang Ruhiyat (The Future of Education Journal, 2026)
This community service activity aims to improve the financial management capabilities of Micro, Small, and Medium Enterprises (MSMEs) through the digitalization of financial recording using the BukuWarung application for MSME actors in Pondok Indah Housing RW 09, Kutabumi Village, Pasar Kemis District, Tangerang Regency. The method applied in this activity consisted of training and mentoring programs, including problem identification, socialization, practical application training, assistance, and evaluation stages. The results of the activity indicate that the BukuWarung application was able to assist MSME actors in recording income and expenses, managing accounts payable and receivable, preparing daily and monthly financial reports, and controlling inventory in a more systematic manner. In addition, the program also increased participants’ understanding of the importance of separating personal finances from business finances. Based on the evaluation results, most participants stated that the training provided positive benefits for managing their businesses. Therefore, the implementation of financial digitalization through the BukuWarung application is considered effective in improving digital literacy and supporting the efficiency of MSME financial management in a sustainable manner.